CO CLUSTER FORMATION IN TiO2 DMS AND A METHOD OF ESTIMATION - Le Van Hong; Nguyen Chi Thuan; Nguyen Van Dai; Nguyen Xuan Phuc (Universitas Gadjah Mada, 2007)
The paper presents experimental observations of the Co cluster formation in TiO2/Co powder samples prepared by the Sol-Gel method. The obtained X-ray diffraction patterns and Raman scattering show that the anatase phase of TiO2 was successfully synthesized at an annealing temperature of 450°C. Comprehensive studies by means of X-ray diffraction, Raman scattering, thermal magnetization in a temperature range of 300–1000 K and magnetic hysteresis at room temperature confirm that a part of Co did not substitute for Ti in TiO2 structure, otherwise it has reasonably formed cluster of Co in samples. Based on the thermal magnetization curves a method to estimate the magnetic moment per one Co ion substituted for Ti in TiO2 structure was proposed. By means of this method the volume of Co substituted for Ti has been estimated for samples annealed at various temperatures around 450°C. The obtained results show that the volume of Co cluster rises when the annealing temperature increases. This obtained result persuasively explains the large divergence in the magnetic moment per one Co ion reported in the most published papers.